Emergência do grupo de pestivírus hobi-like e impacto no diagnóstico e controle do vírus da diarréia viral bovina - Bauermann, Fernando Viçosa (2013)
The genus Pestivirus is composed by four important pathogens of livestock: bovine viral diarrhea virus 1 and 2 (BVDV-1 and BVDV-2), classical swine fever virus (CSFV) and border disease virus (BDV) of sheep. An emerging group of pestivirus temptatively called as HoBi-like, BVDV-3, or atypical pestiviruses was first detected and characterized in Europe from a fetal bovine serum (FBS) lot originated in Brazil. HoBi-like viruses share genetic and antigenic similarities with BVDV species. The present thesis is composed by studies that address the emergence of this virus group and its potential impact on BVDV diagnostic and control. Monoclonal antibody binding demonstrated the existence of conserved regions within epitopes in the glycoprotein Erns and the non-structural protein NS2/3 among the pestiviruses species (BVDV-1; BVDV-2; e HoBi-like), whereas high degree of divergence was detected in glycoprotein E2. These findings suggest that panpestiviruses diagnostic tests may rely on the Erns and NS2/3 proteins, and pestiviruses specific species diagnostic tests should target the E2 glycoprotein. The threshold for detection of HoBi-like virus using commercial BVDV antigen capture ELISA was statistically similar to BVDV detection. On the other hand, two BVDV antibody detection ELISA kits failed to detect at least 20% of animals harboring antibodies against HoBi_D32/00. Thus, it is obvious the need for the development of specific diagnostic tests to HoBi-like viruses. Likewise, it was verified that vaccines containing strains of BVDV-1 and BVDV-2 inactivated or modified live (MLV) virus generate suboptimal protection against HoBi-like viruses. Higher levels of protective antibodies against HoBi-like virus were verified using MLV. Nevertheless the geometric mean titer for HoBi-like was 12.9, while 51.1 and 23.5 for BVDV-1 and BVDV-2, respectively. In addition to low levels of protective antibodies, seroconversion was verified in 68% of animals to HoBi-like virus, although reached 100% and 94% against BVDV-1 and BVDV-2, respectively. Regarding to the diagnostic and control of pestiviruses, the trade of FBS may poses as an important route for dissemination of agents contaminating this product. Composed by a homogenate of serum from hundreds to thousands of fetuses, pestiviruses screening in FBS lots are potentially an important source of information regarding the presence and/or dissemination of these viruses in the region where samples were originated from. Therefore, FBS lots originated in North American countries and processed in the United States of America (USA) or Europe were tested. While several lots were detected as positive for BVDV, none of the lots manufactured in the USA were detected as positive for HoBi-like viruses or antibodies against it. However, two FBS lots processed in Europe were positive for HoBi-like viruses, suggesting that the contamination did occur during the pooling or package of these samples in Europe. These results strongly indicate the need for international rules regarding certification of FBS origin, employment of certified diagnostic tests and measures to avoid contamination of FBS during the manufacturing process. Was also verified the need to include specific tests to detect HoBi-like viruses in the FBS quality control routine. Briefly, the studies here presented demonstrated that the available BVDV diagnostic tests frequently fail in detecting HoBi-like viruses and/or differentiate between HoBi-like virus and BVDV species. In addition, the detection of animal harboring antibodies against HoBi-like using commercial diagnostic tests is unreliable. Likewise, in-vitro studies demonstrated that the cross protection against HoBi-like viruses in serum of animals immunized against BVDV-1 and BVDV-2 is limited. Therefore, the detection and control of this emergent group of viruses require the development of specific diagnostic tests and vaccines.